Pencegahan Anemia pada Remaja di SMK Negeri Bojonggede - Adhila Fayasari; Tri Ardianti Khasanah; Lina Agestika (Jurnal Abdimas Kesehatan (JAK), 2022)
Anemia is well known as micronutrient deficiency, called hidden hunger. West Java has a high prevalence of anemia. The nutrition education program about anemia has been conducted, but the increment was not satisfactory. 10 of 15 female students in Bojong Gede State Vocational School showed a symptom of anemia. Our activity aims to evaluate the effect of a nutrition education program on anemia and reproduction health’ knowledge. This community program was conducted online using power point, video, and games media on 30 students of Bojong Gede State Vocational School, Bogor. Evaluation of the effectiveness of the activity was analyzed using pre and post-tests regarding the knowledge of young women regarding anemia. Statistical analysis used is the Mann-Whitney test. Students' knowledge scores about anemia on the first day increased from 63.21±15.17 to 71.43±13.08 (p = 0.001), and on the second day from 57.14 ± 13.26 to 82.86±17.29 (p = 0.000). More specific topics about healthy food are more attractive to teenagers than more general and contextual topics. Therefore, the practical and applicable knowledge is considered suitable for increasing students' knowledge, especially if it is simultaneously conducted